Analysis On The Level Of Knowledge Among Perak Civil Servants On The Items Of Payable Income Zakah Calculation/ Analisis Tahap Pengetahuan Penjawat Awam di Perak Terhadap Item Item dalam Pengiraan Jumlah Pendapatan Berzakat (Sains Humanika, 2021)
This study aims to determine the level of knowledge on the items of payable income zakah calculation among civil servants in Perak. Quatitative method using the instrument of questionnaire is employed to obtain data in attaing the research objective. Four items of income are studied which are the salary, fixed monthly allowance, overdue salary and bonus by involving 108 respondents. The collected data is then analyzed using the analysis of frequency, percentage and mean. Findings of the study uncover that the level of knowledge among respondents pertaining to the general and specific basic concept of zakah is considerably high. For the item analysis, it is found that the items of overdue salary and bonus are the items which are less known to be included in the calculation of payable income zakah. Therefore, the authority which is the State Islamic Religious Council (MAIN) and zakah centres must diversify the techniques to increase awareness in regard to this gap.
Keywords: Pengetahuan; zakat pendapatan; pengiraan; deskriptif